The Influence of FIQH Science Learning in Improving Religious Understanding in The Midst Of the Covid-19 Pandemic - Sapiudin, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of this study is to see the influence of fiqh learning in improving religious understanding in the midst of the covid-19 pandemic against the background of educational problems in Indonesia today that are considered increasingly complex, the authors seek to study about the learning of fiqh science in the midst of the covid-19 pandemic. In the implementation of this study using quantitative methods, the results of the study of fiqh understanding of students of the State Islamic University of Jakarta, obtained data from the average percentage results of 23.83 % very often, 68% often, 13.37% sometimes and 0% never so that the conclusion that the study of jurisprudence in students of the State Islamic University of Jakarta.